If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1r(x + -1) = 2(7 + -3x) Reorder the terms: 3x + -1r(-1 + x) = 2(7 + -3x) 3x + (-1 * -1r + x * -1r) = 2(7 + -3x) 3x + (1r + -1rx) = 2(7 + -3x) Reorder the terms: 1r + -1rx + 3x = 2(7 + -3x) 1r + -1rx + 3x = (7 * 2 + -3x * 2) 1r + -1rx + 3x = (14 + -6x) Solving 1r + -1rx + 3x = 14 + -6x Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3x' to each side of the equation. 1r + -1rx + 3x + -3x = 14 + -6x + -3x Combine like terms: 3x + -3x = 0 1r + -1rx + 0 = 14 + -6x + -3x 1r + -1rx = 14 + -6x + -3x Combine like terms: -6x + -3x = -9x 1r + -1rx = 14 + -9x Reorder the terms: -14 + 1r + -1rx + 9x = 14 + -9x + -14 + 9x Reorder the terms: -14 + 1r + -1rx + 9x = 14 + -14 + -9x + 9x Combine like terms: 14 + -14 = 0 -14 + 1r + -1rx + 9x = 0 + -9x + 9x -14 + 1r + -1rx + 9x = -9x + 9x Combine like terms: -9x + 9x = 0 -14 + 1r + -1rx + 9x = 0 The solution to this equation could not be determined.
| 6(7n-4)-1=12+5n | | y=0.12x+17.52 | | 5x+72367=109917 | | 2x+1=2y+5 | | 1.25+a=2a+1 | | 7+2x=30 | | 2+y/6=-13 | | (x+2)(5x-4)=0 | | 2x^2=3+9x | | 7x-6=3x+14 | | 10e+2e-9=39 | | 10x-15=6x+30 | | 4x+6=91 | | (x-8)(5x-4)=0 | | 4y+12=6y+14 | | 12j=16j(j-8) | | (3w-4)(4w+6)= | | 3x-2(-5x+3)=72 | | 7+2(7)=30 | | h=0.5s-5 | | 20-5w=60 | | 6-10m=-54 | | 8-3p=-14 | | X+3y=-15 | | 2v^2-14v=0 | | 2+4n=-10 | | 1x-4x=6 | | 10=-5(3+w) | | 7-2n=5 | | 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 |